Pendekatan Konseling Islami dalam Mengatasi Kecemasan Akademik Mahasiswa - Akhmad Sahrandi (Muthmainnah: Jurnal Bimbingan Konseling Islam dan Psikosufistik, 2025)
This study was motivated by the phenomenon of academic anxiety experienced by many students, including those in Islamic universities, which has an impact on their performance, motivation, and psychological well-being. Among Muslim students, this anxiety is often complicated by an internal conflict between academic demands and the belief in tawakkal (trust in God). This qualitative case study aims to examine in depth the application and effectiveness of the Islamic Counseling Approach in overcoming academic anxiety at the Darul Lughah International Islamic University of Pasuruan (UII Dalwa). The results show that the concept of counseling at UII Dalwa is built on the integration of modern psychological principles with Islamic spiritual values, such as tawakal, gratitude, patience, and zikir, which are based on QS Ar-Ra’d: 28 and Religious Coping theory. Its implementation is realized through individual counseling that combines Active Listening with the Qalbī approach, Halaqah Zikir and Muhasabah, as well as Islamic-based stress management training that transforms worldly techniques into worship (sacralization of the mundane). The research findings conclude that this integrative model is not only effective in reducing symptoms of academic anxiety, but also capable of transforming the meaning of difficulties into part of worship, thus representing a constructive dialogue between psychology and religion that offers a holistic and contextual alternative paradigm for Muslim communities.